Financiamento cultural: Uma vis\~ao de princípios - Frederico Barbosa; Roberto Freitas Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper deals with the funding of cultural activities, describing and analyzing the arguments that justify the State's participation in this funding. It analyzes the critics who claim to have been the cultural policies in Brazil left to the market due to the primacy of tax incentives, part of the Rouanet Law. To meet this objective it analyzes the composition of public and private resources and public indirect tax expenditures. The argument unfolds in the reflection on the legitimacy foundations of the state's participation on funding cultural consumption via "Culture Tickets", which is a form of tax incentives, establishing new ideological and principled arguments, expressing the view that the state should subsidize the members of the working class individual choices in relation to the preferences of consumption of cultural goods. Finally, a third aspect is the quality of budget execution flow of the public body. In this case, our hypothesis is that much of the energy expended in criticizing questions of general principles like the preference for the market could be redirected into an effort to reform the state itself. There are many problems in the public decision making process about the state budget and its implementation. Strong initiatives are needed to adjust the amounts of financial resources to cultural needs, but also to improve the quality of the spending process.
Keywords: Z18; 330; culture; state budget; market; public regulation